In situ phosphorylation of the α subunit of eukaryotic initiation factor 2 in reticulocyte lysates inhibited by heme deficiency, double-stranded RNA, oxidized glutathione, or the heme-regulated protein kinase - Ernst, Vivian (1979)
Protein synthesis initiation in reticulocyte lysates is inhibited by heme deficiency, low levels of double-stranded RNA (dsRNA), oxidized glutathione (GSSG), or the purified kinase (HRI) that acts on the α polypeptide of eukaryotic initiation factor 2 (eIF-2α). The phosphoprotein profiles produced in lysates in response to these various conditions have been monitored directly in lysates after labeling for brief periods with pulses of [γ-(32)P]ATP. The [(32)P]phosphoprotein profiles were analyzed by electrophoresis in sodium dodecyl sulfate/polyacrylamide slab gels under conditions in which the HRI and eIF-2α polypeptides were clearly distinguished. All four modes of inhibition produced a rapid phosphorylation of eIF-2α compared to control lysates, which displayed little or no phosphorylation of eIF-2α. In heme-deficient lysates, phosphorylation of eIF-2α occurred rapidly both before and after the shut-off of protein synthesis; the delayed addition of hemin to these lysates resulted in a decrease in the phosphorylation of eIF-2α and the subsequent restoration of protein synthesis. These data suggest that rapid turnover of phosphate occurs at the site(s) of eIF-2α phosphorylation. In lysates inhibited by heme deficiency, GSSG, or added HRI, the phosphorylation of eIF-2α was accompanied by the rapid in situ phosphorylation of HRI. The inhibition of initiation induced by dsRNA was accompanied by the phosphorylation of eIF-2α and a 67,000-dalton polypeptide but not HRI. These observations in situ indicate that (i) the phosphorylation of eIF-2α is the critical event in these inhibitions of protein chain initiation, and (ii) the phosphorylation of HRI is associated with its activation in heme deficiency.